Find the value of $\displaystyle \lim_{n \to \infty }\dfrac{\sqrt{1}+\sqrt{2}+\sqrt{3}+.....+\sqrt{n}}{{{n}^{\dfrac{3}{2}}}}$.
Answer
Verified
409.2k+ views
Hint: Divide both the numerator and the denominator with $\sqrt{n}$ and convert the given sum of infinite terms into a summation series of the form $\displaystyle \lim_{n \to \infty }\sum\limits_{r=1}^{n}{\dfrac{1}{n}f\left( \dfrac{r}{n} \right)}$. Now, in the next step convert this expression of limit into a definite integral by replacing $\left( \dfrac{r}{n} \right)$ with x and $\dfrac{1}{n}$ with $dx$. The upper and lower limits of the integral will be found by substituting r = n and r = 1 in the expression $\displaystyle \lim_{n \to \infty }\left( \dfrac{r}{n} \right)$ respectively and simplifying. Finally, use the formula $\int{{{x}^{n}}dx}=\dfrac{{{x}^{n+1}}}{n+1}$ and substitute the suitable limits to get the answer.
Complete step by step answer:
We have been provided with the expression $\displaystyle \lim_{n \to \infty }\dfrac{\sqrt{1}+\sqrt{2}+\sqrt{3}+.....+\sqrt{n}}{{{n}^{\dfrac{3}{2}}}}$ and we are asked to find its value. Here we need to convert the expression of limit into a definite integration to solve the question. Let us assume the given limit as I, so we have,
$\Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{\sqrt{1}+\sqrt{2}+\sqrt{3}+.....+\sqrt{n}}{{{n}^{\dfrac{3}{2}}}}$
Dividing the numerator and the denominator with $\sqrt{n}$ we get,
\[\begin{align}
& \Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{\left( \dfrac{\sqrt{1}}{\sqrt{n}}+\dfrac{\sqrt{2}}{\sqrt{n}}+\dfrac{\sqrt{3}}{\sqrt{n}}+.....+\dfrac{\sqrt{n}}{\sqrt{n}} \right)}{\left( \dfrac{{{n}^{\dfrac{3}{2}}}}{\sqrt{n}} \right)} \\
& \Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{\left( \sqrt{\dfrac{1}{n}}+\sqrt{\dfrac{2}{n}}+\sqrt{\dfrac{3}{n}}+.....+\sqrt{\dfrac{n}{n}} \right)}{\left( \dfrac{{{n}^{\dfrac{3}{2}}}}{{{n}^{\dfrac{1}{2}}}} \right)} \\
\end{align}\]
Using the formula of exponents given as $\dfrac{{{a}^{m}}}{{{a}^{n}}}={{a}^{m-n}}$ in the denominator we get,
\[\begin{align}
& \Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{\left( \sqrt{\dfrac{1}{n}}+\sqrt{\dfrac{2}{n}}+\sqrt{\dfrac{3}{n}}+.....+\sqrt{\dfrac{n}{n}} \right)}{{{n}^{\dfrac{3}{2}-\dfrac{1}{2}}}} \\
& \Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{\left( \sqrt{\dfrac{1}{n}}+\sqrt{\dfrac{2}{n}}+\sqrt{\dfrac{3}{n}}+.....+\sqrt{\dfrac{n}{n}} \right)}{n} \\
& \Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{1}{n}\left( \sqrt{\dfrac{1}{n}}+\sqrt{\dfrac{2}{n}}+\sqrt{\dfrac{3}{n}}+.....+\sqrt{\dfrac{n}{n}} \right) \\
\end{align}\]
In the summation form we can write the expression as: -
\[\Rightarrow I=\displaystyle \lim_{n \to \infty }\sum\limits_{r=1}^{n}{\dfrac{1}{n}\left( \sqrt{\dfrac{r}{n}} \right)}\]
Now, we know that any limit of the form $\displaystyle \lim_{n \to \infty }\sum\limits_{r=1}^{n}{\dfrac{1}{n}f\left( \dfrac{r}{n} \right)}$ can be converted into a definite integral by replacing $\left( \dfrac{r}{n} \right)$ with x and $\dfrac{1}{n}$ with $dx$. So, the limit can be written as: -
\[\Rightarrow I=\int{\sqrt{x}dx}\]
Here, we need to determine the limits of this integral. To do this, we substitute r = n and r = 1 in the expression $\displaystyle \lim_{n \to \infty }\left( \dfrac{r}{n} \right)$ respectively and simplify. So the upper limit will be $\displaystyle \lim_{n \to \infty }\left( \dfrac{n}{n} \right)=1$ and the lower limit will be $\displaystyle \lim_{n \to \infty }\left( \dfrac{1}{n} \right)=0$. Therefore the integral becomes: -
$\Rightarrow I=\int_{0}^{1}{{{x}^{\dfrac{1}{2}}}dx}$
Using the formula $\int{{{x}^{n}}dx}=\dfrac{{{x}^{n+1}}}{n+1}$ we get,
$\begin{align}
& \Rightarrow I=\left[ \dfrac{{{x}^{\dfrac{1}{2}+1}}}{\dfrac{1}{2}+1} \right]_{0}^{1} \\
& \Rightarrow I=\left[ \dfrac{{{x}^{\dfrac{3}{2}}}}{\dfrac{3}{2}} \right]_{0}^{1} \\
& \Rightarrow I=\dfrac{2}{3}\left[ {{x}^{\dfrac{3}{2}}} \right]_{0}^{1} \\
\end{align}$
Substituting the suitable limits and simplifying we get,
$\begin{align}
& \Rightarrow I=\dfrac{2}{3}\left[ {{1}^{\dfrac{3}{2}}}-{{0}^{\dfrac{3}{2}}} \right] \\
& \Rightarrow I=\dfrac{2}{3}\left[ 1 \right] \\
& \therefore I=\dfrac{2}{3} \\
\end{align}$
Hence, the value of the given limit is $\dfrac{2}{3}$.
Note: It is necessary to convert the given limit into a definite integral because there is no direct formula in limits which can be applied to solve the question. Do not apply L'Hospital's rule to get the answer. Remember that the formula $\int{{{x}^{n}}dx}=\dfrac{{{x}^{n+1}}}{n+1}$ cannot be applied for n = -1 because if n = -1 then the function becomes $\dfrac{1}{x}$ whose integral is $\ln x$.
Complete step by step answer:
We have been provided with the expression $\displaystyle \lim_{n \to \infty }\dfrac{\sqrt{1}+\sqrt{2}+\sqrt{3}+.....+\sqrt{n}}{{{n}^{\dfrac{3}{2}}}}$ and we are asked to find its value. Here we need to convert the expression of limit into a definite integration to solve the question. Let us assume the given limit as I, so we have,
$\Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{\sqrt{1}+\sqrt{2}+\sqrt{3}+.....+\sqrt{n}}{{{n}^{\dfrac{3}{2}}}}$
Dividing the numerator and the denominator with $\sqrt{n}$ we get,
\[\begin{align}
& \Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{\left( \dfrac{\sqrt{1}}{\sqrt{n}}+\dfrac{\sqrt{2}}{\sqrt{n}}+\dfrac{\sqrt{3}}{\sqrt{n}}+.....+\dfrac{\sqrt{n}}{\sqrt{n}} \right)}{\left( \dfrac{{{n}^{\dfrac{3}{2}}}}{\sqrt{n}} \right)} \\
& \Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{\left( \sqrt{\dfrac{1}{n}}+\sqrt{\dfrac{2}{n}}+\sqrt{\dfrac{3}{n}}+.....+\sqrt{\dfrac{n}{n}} \right)}{\left( \dfrac{{{n}^{\dfrac{3}{2}}}}{{{n}^{\dfrac{1}{2}}}} \right)} \\
\end{align}\]
Using the formula of exponents given as $\dfrac{{{a}^{m}}}{{{a}^{n}}}={{a}^{m-n}}$ in the denominator we get,
\[\begin{align}
& \Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{\left( \sqrt{\dfrac{1}{n}}+\sqrt{\dfrac{2}{n}}+\sqrt{\dfrac{3}{n}}+.....+\sqrt{\dfrac{n}{n}} \right)}{{{n}^{\dfrac{3}{2}-\dfrac{1}{2}}}} \\
& \Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{\left( \sqrt{\dfrac{1}{n}}+\sqrt{\dfrac{2}{n}}+\sqrt{\dfrac{3}{n}}+.....+\sqrt{\dfrac{n}{n}} \right)}{n} \\
& \Rightarrow I=\displaystyle \lim_{n \to \infty }\dfrac{1}{n}\left( \sqrt{\dfrac{1}{n}}+\sqrt{\dfrac{2}{n}}+\sqrt{\dfrac{3}{n}}+.....+\sqrt{\dfrac{n}{n}} \right) \\
\end{align}\]
In the summation form we can write the expression as: -
\[\Rightarrow I=\displaystyle \lim_{n \to \infty }\sum\limits_{r=1}^{n}{\dfrac{1}{n}\left( \sqrt{\dfrac{r}{n}} \right)}\]
Now, we know that any limit of the form $\displaystyle \lim_{n \to \infty }\sum\limits_{r=1}^{n}{\dfrac{1}{n}f\left( \dfrac{r}{n} \right)}$ can be converted into a definite integral by replacing $\left( \dfrac{r}{n} \right)$ with x and $\dfrac{1}{n}$ with $dx$. So, the limit can be written as: -
\[\Rightarrow I=\int{\sqrt{x}dx}\]
Here, we need to determine the limits of this integral. To do this, we substitute r = n and r = 1 in the expression $\displaystyle \lim_{n \to \infty }\left( \dfrac{r}{n} \right)$ respectively and simplify. So the upper limit will be $\displaystyle \lim_{n \to \infty }\left( \dfrac{n}{n} \right)=1$ and the lower limit will be $\displaystyle \lim_{n \to \infty }\left( \dfrac{1}{n} \right)=0$. Therefore the integral becomes: -
$\Rightarrow I=\int_{0}^{1}{{{x}^{\dfrac{1}{2}}}dx}$
Using the formula $\int{{{x}^{n}}dx}=\dfrac{{{x}^{n+1}}}{n+1}$ we get,
$\begin{align}
& \Rightarrow I=\left[ \dfrac{{{x}^{\dfrac{1}{2}+1}}}{\dfrac{1}{2}+1} \right]_{0}^{1} \\
& \Rightarrow I=\left[ \dfrac{{{x}^{\dfrac{3}{2}}}}{\dfrac{3}{2}} \right]_{0}^{1} \\
& \Rightarrow I=\dfrac{2}{3}\left[ {{x}^{\dfrac{3}{2}}} \right]_{0}^{1} \\
\end{align}$
Substituting the suitable limits and simplifying we get,
$\begin{align}
& \Rightarrow I=\dfrac{2}{3}\left[ {{1}^{\dfrac{3}{2}}}-{{0}^{\dfrac{3}{2}}} \right] \\
& \Rightarrow I=\dfrac{2}{3}\left[ 1 \right] \\
& \therefore I=\dfrac{2}{3} \\
\end{align}$
Hence, the value of the given limit is $\dfrac{2}{3}$.
Note: It is necessary to convert the given limit into a definite integral because there is no direct formula in limits which can be applied to solve the question. Do not apply L'Hospital's rule to get the answer. Remember that the formula $\int{{{x}^{n}}dx}=\dfrac{{{x}^{n+1}}}{n+1}$ cannot be applied for n = -1 because if n = -1 then the function becomes $\dfrac{1}{x}$ whose integral is $\ln x$.
Recently Updated Pages
Master Class 11 Accountancy: Engaging Questions & Answers for Success
Glucose when reduced with HI and red Phosphorus gives class 11 chemistry CBSE
The highest possible oxidation states of Uranium and class 11 chemistry CBSE
Find the value of x if the mode of the following data class 11 maths CBSE
Which of the following can be used in the Friedel Crafts class 11 chemistry CBSE
A sphere of mass 40 kg is attracted by a second sphere class 11 physics CBSE
Trending doubts
10 examples of friction in our daily life
Difference Between Prokaryotic Cells and Eukaryotic Cells
One Metric ton is equal to kg A 10000 B 1000 C 100 class 11 physics CBSE
State and prove Bernoullis theorem class 11 physics CBSE
What organs are located on the left side of your body class 11 biology CBSE
Define least count of vernier callipers How do you class 11 physics CBSE